Iatrogenic pseudoaneurysm of inferior epigastric artery: not only a surgical complication - Rossana Corso; Andrea Coppola; Stefano Grazioli; Cristina Dedionigi; Nicolò Tandurella; Massimo Venturini; Francesco Dentali (Bleeding, Thrombosis and Vascular Biology, 2022)
A 77-year-old lady with a longstanding scleroderma, presented to the Emergency Department for a state of severe malnutrition and fluid dysphagia. On physical examination, she presented an abdominal palpable swelling, with an associated large, posterior ecchymosis. A pseudoaneurysm of the right inferior epigastric artery was diagnosed on a color Doppler ultrasound examination. After collegial discussion with the surgical and interventional-radiologist team, a percutaneous exclusion of the pseudoaneurysm through thrombin injection was successfully performed, and no complications were reported. After a thorough anamnestic record, the possible cause of the pseudoaneurysm was discovered: a few days before hospital admission the general practitioner did some intradermoclysis in the abdominal wall to hydrate the patient, damaging the inferior epigastric artery wall with subsequent development of the pseudoaneurysm. The patient completely recovered, returned home after two weeks in a subacute facility, and is awaiting evaluation for the scleroderma follow up from a rheumatologist.